Paritaprevir/ritonavir-ombitasvir and dasabuvir, the 3D regimen for the treatment of chronic hepatitis C virus infection: a concise review - Hussaini T (Dove Medical Press, 2016)
Trana Hussaini1,2 1Faculty of Pharmaceutical Sciences, University of British Columbia, Vancouver, BC, Canada; 2Pharmaceutical Sciences, Vancouver General Hospital, Vancouver, BC, Canada Abstract: The treatment for chronic hepatitis C has been revolutionized with the development of direct-acting antiviral agents. Several regimens have been approved and are currently used in clinical practice, treating a wide range of patient populations infected with hepatitis C. The interferon-free combination of paritaprevir/ritonavir-ombitasvir and dasabuvir (PrOD or the three-drug [3D] regimen) with or without ribavirin is indicated for the treatment of chronic hepatitis C in both treatment-naïve and experienced patients infected with genotype 1, including those coinfected with HIV and patients post-liver transplantation. More recently, paritaprevir/ritonavir-ombitasvir (PrO, or 2D regimen) has been approved in hepatitis C virus patients infected with genotype 4. This review will summarize pharmacokinetic and clinical efficacy data for the 3D regimen in an attempt to help the clinicians delineate its place in the ever-increasing direct-acting antiviral armamentarium for the treatment of chronic hepatitis C. Keywords: hepatitis C, paritaprevir, ombitasvir, dasabuvir, 3D regimen